World economy at the crossroads - Johnson, Harry G. (Oxford, 1966)
The world economy that the postwar planners of Bretton Woods sought to reconstruct has reached a crossroads. The institutions established at Bretton Woods have been largely by-passed by events, and the question is whether new arrangements will be evolved in con formity with the spirit of Bretton Woods or the international economy will dis integrate into a world of rival economic blocs. This book describes the back ground of Bretton Woods, the postwar evolution of the international economic system, and the outstanding issues in the field of international monetary arrangements, international trading arrangements, and policies for pro moting the economic growth of the developing countries. All of these issues are viewed in the perspective of the requirements of an international econo mic order that will foster the stability and growth of the world economy.
Keywords: Economics